(untitled) (Journal of NELTA, 2024)
The COVID-19 pandemic brought unprecedented challenges, starting in early 2020 and leading to the extensive shutdown of schools around the globe, necessitating a rapid transition to an alternative mode of teaching and learning. Amidst the digital divide regarding access and skills, shifting to virtual teaching-learning was a challenge in Nepal that caused a lot of stress for teachers. This study explores the emotional experiences of basic-level English language teachers in private schools as they adapted to this unforeseen shift. The study investigates the experiences of the English language teachers elicited through in-depth interviews and informal conversation particularly the impact of COVID-19, the sudden shift to virtual instruction on teachers’ emotional well-being and how they adapted to this new normal. The research result revealed that they felt unprecedented psychological needs and fear, underwent loneliness and social isolation, experienced teaching challenges, uncertainty and anxiety, and frustration and helplessness. Despite these challenges, they also showed emotional resilience through peer support and collaboration, family support and work-life balance, and adaptation of new technology and innovation in teaching and learning. This article informs teachers, policymakers, and practitioners about the emotional upheavals teachers experienced during the crises and the resilience displayed, implying policy formulation and teacher support mechanisms.